MATHEMATICS IN CHEMISTRY (ResearchJet Journal of Analysis and Inventions, 2021)
Chemical problems and exercises serve as an important didactic means in the formation and development of mental and practical skills based on the theoretical knowledge acquired by students. In order to master the skills of solving chemical problems and exercises, it is important that students have a thorough theoretical knowledge and be able to perform various types of mental activities.